Compaction characteristics of Ficus Deltoidea jack extract powder - Mohd Salleh, Faiqa Shazeaa (2012)
In Malaysia, Ficus deltoidea is locally known as Mas Cotek and is traditionally used to treat cardiovascular diseases, diabetes, and as an aphrodisiac specifically to increase male virility. The main objective of this thesis is to investigate the compressibility and compactability of Ficus deltoidea extract powders for tableting processes. Avicel and Acdisol powders are used as excipients. Both of these powders are essentially easily soluble and disintegrate in water. The physical, material and flow properties of the powders have been investigated as it is essential to understand the compression and compaction mechanisms. The Ficus deltoidea extract powder has a particle size of less than 40 μm and was compressed into a tablet by using a 13-mmcylindrical uniaxial die. Applied pressures between 7.53 to 73.84 MPa were adopted using a universal testing machine. To further investigate the properties, the friability and modified dissolution tests were carried out. This was aimed to provide a convenient soluble form for consumers who have difficulties in swallowing tablets and chewing difficulties, whereby the tablet can dissolve easily in water and can be drunk directly. From the tests, tablets composed of Acdisol had a faster dissolve time in the modified dissolution time test compared to Avicel. Based on these stud ies, a few recommended tablet conditions have been classified from the best conditions of compression and compaction characteristic tablet. The best formulation for the tablets was a combination of 50 % and 70 % of Avicel and Acdisol with Ficus deltoidea extract powder respectively at a pressure of 73.84 MPa. As a safety measure before consumption, these three main material powders were chosen for a toxicity test, utilizing an in vitro technique for testing cancer toxicity on human cells. Thus, this study provides information concerning the extent of the application of compression and compaction characteristics for product development of Ficus deltoidea extract as a safe and healthy supplement.